ANALISIS PENERAPAN ISO 14001 UNTUK MENUNJANG KESELAMATAN KERJA PADA PT. UNITED STEEL CENTER MENGGUNAKAN METODE HAZARD IDENTIFICATION, RISK ASSESMENT AND RISK CONTROL (HIRARC) - Naufal Fais Lazuardi (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2023)
PT. United Steel Center Indonesia-Karawang is a company engaged in manufacturing that focuses on blanking steel coins for automotive or non-automotive. The TKG and TWB departments were chosen to be the object of research based on data regarding the highest number of work accident incidents in 2021 and there are still manual processes involving humans. The method used is the HIRARC method, a method that combines hazard identification, risk assessment, and risk control to avoid or minimize work accidents. There are 3 problems that occur in the TKG department and 2 problems in the TWB department. Therefore, it is necessary to update the SOP, especially regarding the use of PPE, which replaces the safety hand and safety leg with a universal size so that it can adjust to the size of each employee's hands and feet, adding earmuff PPE for noisy work, wearing a Gas Respirator mask for anti-oiling work. rust, and the use of safety hands during the input welding process.Keywords: HIRARC; Work Accident ;PPE.